Unique Genomic Profile Associated with Pediatric Uveal Melanoma. Issue 4 (July 2015) - Blasi, Maria Antonietta; Orteschi, Daniela; Pagliara, Monica M.; Coco, Giulia; Asaro, Alessia; Mulè, Antonino; Petrone, Gianluigi; Zollino, Marcella
Purpose: To determine genetic features of a pediatric uveal melanoma in a 6-year-old girl by array-based comparative genomic hybridization (a-CGH) and assess prognosis, and to search for constitutional copy number variations (CNVs) encompassing oncosuppressor genes. Methods: High-resolution a-CGH was performed on genomic DNA from cancer cells and from peripheral blood cells. Histopathology and clinical staging of the tumor were simultaneously assessed. Results: Array-based CGH revealed no CNVs on tumor cells associated with poor prognosis; namely, no monosomy 3, losses of 1p, 6q, or 8p, and no gains of 8q. A unique genomic profile was observed, consisting mainly of partial terminal duplications affecting chromosomes 1, 4, 5, 9, 10, 11, 16, and 19, and complete trisomy of chromosomes 6, 7, and 20. The nonmetastatic tumor had predominantly epithelioid histology. No constitutional CNVs encompassing oncosuppressor genes were detected. Conclusions: We report a very rare uveal melanoma characterized by low-risk genomic profile and poor prognostic histologic and clinical features. The child is relapse-free at 1-year follow-up. The unusual CNVs detected by a-CGH suggest specific pathogenic mechanisms.